Development of testbed for cyber-manufacturing security issues. Issue 3 (3rd March 2020) - Wu, Mingtao; Song, Jinwoo; Sharma, Snehav; Di, Jupeng; He, Benliu; Wang, Ziming; Zhang, Jingkai; Lin, Long Wang Lucas; Greaney, Emily Ann; Moon, Young
ABSTRACT: Future manufacturing systems such as Industry 4.0, Cloud Manufacturing, or Cyber-Manufacturing System (CMS) rely on the seamless integration of cyber and physical domains in the manufacturing systems. However, this increased connectivity within a factory and between factories enlarges the attack surface for malicious individuals. Potential intrusions – especially cyber-physical attacks – can cause profound damages to the manufacturing system. In order to detect, prevent and overcome the cyber-physical attacks, an experimental environment to investigate cyber-physical attacks in CMS was developed. This paper presents details of a testbed, called Cyber-Manufacturing System Security Testbed (CSST). It was designed to investigate cyber-physical intrusions and validate their detection methods in the CMS environment. Cyber and physical components of the CSST are described along with how they interact and are constructed to address the security issues. Results from using the CSST at both component and system levels are analyzed and presented.